(untitled) (Saptagandaki Journal, 2020)
The aim of this review was to synthesize the aggregated studies aimed at improving health care knowledge, detection practices and management of dementia among healthcare professionals (HPs). Healthcare professionals play a key role in the detection and management of dementia. However, there is a gap in the literature as to what represents best practice with regard to educating HPs in this area. We searched citation index Google scholar, Scopus and Pub Med, Medline, were searched for relevant articles from 2000-2019 without data limit. Inclusion criteria were (1) intervention studies aimed at improving HPs practices concerning dementia care (2) the educational intervention focused on knowledge, detection practice and management of dementia, and (3) peer-reviewed and written in English. Of 4968 articles identified, only 13 articles (six GPs, two clinical/organization care based, one nurse, one physician and affiliated staff and one with physician, manager and therapists based studies) were suitable for inclusion and these all were from developed countries. Seven studies were randomized controlled trials (RCTs), 1 prospective, 2 GPs and supervisors intervention, 1 cohort study, and 2 clinical /organizational care services clustered randomized study. Overall, the methodological quality of these studies was poor, particularly with regard to the methods utilized and sample sizes however, combined programs of, practice based workshops with community and multi-faced educational program were the most effective. The continuous educational intervention program can improve the health professionals’ diagnosis and management knowledge, confidents and negative perception of dementia. HPs should be Interventions Aimed at Improving Knowledge, Detection Practices and Management of Dementia among Health Professionals. Dr. Pushkar Singh Raikhola1 Dr. Krishna Prasad Pathak2 Tara Gaire3 1 Monitoring Directorate, Tribhuban University, Nepal 2 Nepal Open University, Nepal. Alzheimer Related Dementia Society Nepal. 3 Department of Nursing, Innovative health science college THE SAPTAGANDAKI JOURNAL 2055 B.S. Review Article148 The Saptagandaki Journal / Vol.Xi / Issue 11/ November 2020 / ISSN 2594-3243 (Print) supported to improve their knowledge, tackle behavioral problems associated with dementia, be made aware of services and be enabled to engage in more early diagnosis in primary care. Further intervention program should address the cultural change to facilitate long term improvements. Educational intervention program is crucial to the health professionals to get close to the diagnostic confidence.